Pengembangan Bahan Ajar Modul Sistem Reproduksi Pada Mata Pelajaran Biologi Kelas XI di SMA Putra Al-Azhar - Reza Ardiansyah (Universitas Nahdlatul Ulama Pasuruan, 2020)
Based on the results of observations at SMA Putra Al Azhar, it shows that when learning students have difficulty in Biology lessons, especially material on the reproductive system. Students' learning difficulties are due to the fact that all students are boarding school children, the activities of the boarding school are very dense, students are not allowed to hold cellphones, students only have student worksheets from school which contain very short material. Based on the results of interviews with teachers, it is stated that teachers are very difficult without books or modules to help learning. The teacher should explain more because the students are not prepared to study at all. Based on the results of the questionnaire given to students and teachers, it shows that the development of practical teaching materials is needed to support learning. The module was chosen because it can facilitate students to learn, both with the teacher and independently. The purpose of this study was to produce teaching materials for reproductive system materials at SMA Putra Al-Azhar Pasuruan. The development of teaching materials uses the Four-D development model. Data analysis in the form of descriptive qualitative and quantitative descriptive data. The results of the development of teaching materials in the form of the Reproductive System Module. The teaching materials in the form of modules have been revised based on the validation results from expert validators and small group trials. Based on the percentage of validity obtained from material expert validators and small group trials, the Reproductive System Module developed has met the valid criteria and can be used with a percentage gain of 89.7%. Product revisions were made based on comments and suggestions given in small group trials. This Reproductive System module is equipped with instructions for use, discussions, assignments, summaries, test questions, reflections, answer keys, assessments, and a glossary.